Lack of experience is a significant factor in the missed diagnosis of perilunate fracture dislocation or isolated dislocation - Ilker Çolak; Halil I. Bekler; Güven Bulut; Engin Eceviz; Deniz Gülabi; Gültekin S. Çeçen (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The aim of this study was to analyze the risk factors contributing to the misdiagnosis of perilunate injuries. Methods: The study included patients who had perilunate dislocation or fracture dislocation correctly or incorrectly diagnosed on initial examination between 2008 and 2014. Data related to the length of time until correct diagnosis of the perilunate injury; cause of injury; presence of associated fractures, polytrauma or concomitant trauma in the ipsilateral upper extremity; time between injury and first presentation; first treatment applied; presence of ligamentous perilunar injuries only or fracture and dislocation; inadequate radiographic assessment; and experience of the physicians were recorded and analyzed. Results: A total of 44 wrists were included in the study. Of those, 10 (22.7%) wrists (mean patient age: 44.4 years [28 ± 58 years]) with perilunate injuries were misdiagnosed in the initial evaluation. All of the risk factors were found to be similar between the group of patients with correct initial diagnosis and missed diagnosis group, except for the experience of the orthopedic surgeon assessing the injury (p = 0.0001). Of the surgeons who missed the diagnosis, 70% reported that it was their first encounter with a perilunate injury. Conclusion: The results of this study indicated that lack of experience was the most important factor in the misdiagnosis of perilunate fracture dislocation or isolated dislocation. Level of Evidence: Level IV, diagnostic study. Keywords: Dislocation, Lunate, Perilunate, Wrist injury, Scaphoid fracture, Trans-scaphoid